Development of a Quantitative Diagnostic Criterion for Gastric Linitis Plastica: Findings From a Large Single-Institutional Study - Han, Yang; Xuan, Yi; Liu, Xiaowen; Zhu, Hui; Zhang, Meng; Xu, Dazhi; Wang, Yanong; Cai, Hong (Frontiers in Oncology, 2021)
Gastric linitis plastica (GLP) is a descriptive term but lacks a quantitative definition. Several relatively quantitative criteria had been proposed, such as tumor involving a limit of one-third or two-thirds of the gastric surface. However, these criteria needed doctors to subjectively judge tumor infiltration area, which made diagnosis difficult to be objective and reproducible. This study aimed to propose a quantitative diagnostic criterion for distinguishing GLP. We performed a retrospective cohort study of 2,907 patients with Borrmann III and IV gastric cancer (GC) who underwent gastrectomy between 2011 and 2018 in our center. The Kaplan–Meier curves showed that patients with an observed tumor size more than 8 cm had obviously lower overall survival (OS) and disease-free survival (DFS) rates than those with a size less than 8 cm(p < 0.001; p < 0.001). However, there was no significantly different prognosis of patients with tumor sizes between more than 8 cm and more than 10 cm (p = 0.248; p = 0.534). Moreover, patients with tumor sizes greater than 8 cm more presented with advanced stage and had extremely poor 3-year OS and DFS (31.4%; 29.3%), with a stronger propensity toward peritoneal metastasis. Therefore, we considered patients’ observed tumor size more than 8 cm as a critical value for distinguishing the prognosis of Borrmann III and IV GC. Furthermore, we proposed an observed tumor size more than 8 cm as a quantitative diagnostic criterion for GLP on the premise of satisfying the originally descriptive and pathological definition regardless of Borrmann type.